Poder e dinâmicas de colaboração na governança de empresas sociais - Dal Bó, Gicelda Julia (2021)
This thesis relates power to collaborative dynamics in the context of Social Corporate Governance, with concepts brought from Collaborative Governance and studies of power that argue that the conditions for domination are also the same for empowerment, which make them both visible as members of a family. It is argued that power is not just an available resource of the dynamics of the capacity for joint action, which is one of three collaborative dynamics among the essential components of collaborative governance systems. Instead, power is an ability, inherent in social relationships, that manifests and acts simultaneously in the dynamics of collaboration and presents different meanings in the light of circumstances and interactions in which it is inserted. In developing this perception, we propose an analysis framework that considers the presence of a dimension of power which, by consensus or conflict, manifests itself in the context of a dimension of collaboration where dynamics of collaboration interact in constant development. The thesis explores how the three ways of exercise of power - "power over", "power to" and "power with" - arise through the analysis of the four elements of each of the three dynamics of collaboration - principled engagement, shared motivation, and capacity for joint action. This study depicts a qualitative research with an interpretative and exploratory approach that uses content analysis as a methodological tool. The results indicate that the governance of social enterprises also integrates, in their processes, the same set of collaborative dynamics proposed for broader systems designated as systems of collaborative governance. This given, we also recognize the arguments used for approaches to consensus or conflict through the three ways of exercise power, in the context of the social enterprise’s governance analyzed. It aims to bring a perspective of power to governance studies of social enterprises contributing to broaden its scope.